Over 90% of Childhood BCG Vaccine-Induced Keloids in Japan Occur in Women - Chikage Noishiki; Yoshiaki Hayasaka; Ryu Yoshida; Rei Ogawa (Adis, Springer Healthcare, 2023)
Abstract Introduction Keloids are a fibroproliferative, multifactorial, cutaneous disorder whose pathophysiology is not completely understood. Various factors such as high blood pressure, pregnancy, female gender, mechanical tension of local sites, and prolonged wound healing are known to worsen keloids. Childhood-onset keloids are keloids that form before 10 years of age, before various factors in adulthood come into play, and thus studying childhood-onset keloids may provide additional insight into the underlying mechanisms that lead to keloid formation. Methods Retrospective chart review was performed on all patients with childhood-onset keloids who were evaluated at our plastic surgery clinic (one of the largest keloid referral centers in Japan) over a 1-year period. Results Of the 1443 patients with diagnosis of keloids, 131 patients had childhood-onset keloids. Of these, 106 patients (80.9%) were female, 38.9% of patients had family history of keloids, and 48.9% of patients had allergies or allergy-related conditions (asthma, atopic dermatitis, or allergic rhinitis). Vaccination (47.5%) and chickenpox (19.9%) were the most common triggers. Of vaccinations, BCG was the most common trigger. The majority of keloids from BCG were in female patients (92.9%). The most common location was the chest in male patients (30.0%) and the arm in female patients (41.1%). Conclusion To our knowledge, this is the largest report in the literature on childhood-onset keloids. There was overall female predominance in childhood-onset keloids, and even more significant female predominance in BCG-induced keloids.